Hubungan Karakter Disiplin dengan Prestasi Belajar - Nurmala Azizah; Syukron Ma'mun; Riyanto Riyanto (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2021)
This research was conducted to determine whether there is a relationship between teenagers and student morals. The type of research used in this research is (Field Research) or field research with a quantitative approach, data collection techniques, namely by questionnaires, documentation, and interviews. The sample in the study was 30 people with the Proportionate stratified random sampling technique. The data obtained were analyzed using the Product Moment correlation coefficient. Based on the results of data analysis with Product Moment correlation, the results obtained by the value of r_xy = 0.71, the value of r_xy = 0.71, whose magnitude ranges from 0.70 to 0.90 indicates that there is a positive correlation or relationship between variable X and variable Y and including at a strong or high correlation.r table at a significance level of 5% = 0.374 and a significance level of 1% = 0.478 with df = 28, this indicates that r_xy is greater than r table (rxy> r table) both at the 5% significance level (0.71> 0.374) and a significance level of 1 % (0.71> 0.478). So it can be concluded that there is a strong correlation or relationship between emotional intelligence and the learning achievement of class V MIS Mathlaul Anwar Bojonggede.